Modeling, Simulation and Control of Electrical Drives - Rahman, Muhammed Fazlur; Dwivedi, Sanjeet Kumar (The Institution of Engineering and Technology, 2019)
The following topics are dealt with: machine control; machine vector control; synchronous motor drives; permanent magnet motors; induction motor drives; torque control; sensorless machine control; PWM invertors; PWM power convertors; and closed loop systems.
Keywords: Control theory.; Electric inverters.; Permanent magnet motors.; Pulse modulation (Electronics); elektronické knihy; electronic books